PENGARUH KEPERCAYAAN DAN UMUR TERHADAP KINERJA INDIVIDUAL DALAM PENGGUNAAN TEKNOLOGI INFORMASI - RAINO WIRJONO, ENDANG (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 1 (2010), 2010)
The goal of this research is to examine the effect of ones’ intrinsic variable on the use of information technology at work as well as the motives on using information technology to succeed at work. The multiple regression analysis is used to test three hypotheses. The result shows that trust can effect ones’ performance in using information technology which support previous study performed by Jumali (2005). The result also proves that intrinsic factors shape ones’ self efficacy in using information technology.
Keywords: performance, beliefs, age, technology information